2020
DOI: 10.1177/2324709620936832
|View full text |Cite
|
Sign up to set email alerts
|

Slow on the Uptake, Progression to Heartbreak

Abstract: The prevalence of serotonin syndrome increases over the past several years as more serotonergic medications are being used in clinical practice. It is a potentially lethal condition caused by excessive serotonergic activity. Common causes of serotonin syndrome are the use of prescription medications, illicit drugs, or a combination of substances, leading to an increase in the activity of serotonin in the central and peripheral nervous system. The clinical symptoms range from mild to severe. We report a case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Symptoms are also used to guide the differential diagnosis of the two syndromes; for example: in NMS, patients may have stiffness, rhabdomyolysis (characterized by muscle fiber destruction), and increased serum creatine phosphokinase (CPK) levels, which should not occur in SS [90]. However, some SS case reports show that patients present rigidity, sometimes associated with hyperreflexia [91][92][93][94] and increased serum CPK levels [92,95,96]. In the meta-analysis carried out by Werneke et al (2016), with all cases of SS published in the PubMed databases and Thomson Reuter's Web of Science from 2004 to 2014, they observed that in the 299 cases of SS included in the study, 45.4% (136 cases) had stiffness, and 14% had rhabdomyolysis (42 cases) [5].…”
Section: Serotonin Syndrome Versus Neuroleptic Malignant Syndromementioning
confidence: 99%
“…Symptoms are also used to guide the differential diagnosis of the two syndromes; for example: in NMS, patients may have stiffness, rhabdomyolysis (characterized by muscle fiber destruction), and increased serum creatine phosphokinase (CPK) levels, which should not occur in SS [90]. However, some SS case reports show that patients present rigidity, sometimes associated with hyperreflexia [91][92][93][94] and increased serum CPK levels [92,95,96]. In the meta-analysis carried out by Werneke et al (2016), with all cases of SS published in the PubMed databases and Thomson Reuter's Web of Science from 2004 to 2014, they observed that in the 299 cases of SS included in the study, 45.4% (136 cases) had stiffness, and 14% had rhabdomyolysis (42 cases) [5].…”
Section: Serotonin Syndrome Versus Neuroleptic Malignant Syndromementioning
confidence: 99%